2019
DOI: 10.1038/s41396-019-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

A modular atomic force microscopy approach reveals a large range of hydrophobic adhesion forces among bacterial members of the leaf microbiota

Abstract: Bacterial adhesion is the initial step in surface colonization and community formation. At the single-cell level, atomic force microscopy (AFM) techniques have enabled the quantification of adhesive forces between bacteria and substrata. However, conventional techniques depend on the irreversible immobilization of cells onto cantilevers, thus hampering throughput. Here, we developed a modular AFM method to reversibly immobilize functionalized beads as surface mimic and to probe adhesion of individual bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…These findings are in agreement with those of previous studies [46,47]. Surface hydrophobicity can promote irreversible bacterial adhesion [48]. Although the presence of surface grooves increases the surface area for bacterial adhesion, the increase of hydrophilicity due to the presence of grooves likely reduced bacterial adhesion [49].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with those of previous studies [46,47]. Surface hydrophobicity can promote irreversible bacterial adhesion [48]. Although the presence of surface grooves increases the surface area for bacterial adhesion, the increase of hydrophilicity due to the presence of grooves likely reduced bacterial adhesion [49].…”
Section: Discussionsupporting
confidence: 92%
“…The FluidFM has been used to study the elasticity and adhesion of several cell types [15][16][17][18]. Studies addressing specifically the adhesion of bacterial cells include the work of Potthoff et al [19], Sprecher et al [20] and Mittelviefhaus et al [21]. Potthoff et al further showed that bacteria still divided after SCFS measurements using the FluidFM and thus had survived the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…More than 700 FD-curves were recorded, the highest force values are around 50 nN of the members from Gammaproteobacteria.The nominal spring constant value for micropipette cantilevers was used as 0.2 Nm −1 . InvOLS was recalibrated after each bead exchange, but exact values are not given. 33 Force evaluation of different particle sizes grabbed by FluidFM micropipette and nanopipette cantilevers. Silica particles with diameters of 0.5 µm, 1 µm and 4.3 µm were used.The nominal spring constant values were used for micropipette (0.3 and 2 Nm −1 ) and nanopipette (0.6 Nm −1 ) cantilevers.…”
Section: Introductionmentioning
confidence: 99%